Strategi Investasi Saham Jangka Pendek Menggunakan Average Directional Index, Directional Movement Index, dan Average True Range Pada Pasar Sideways Pada PT. Bukit Asam Tbk - Ichsan Alif Setiawan; Iqbal Nur Fajar; Tine Badriatin (The Indonesia Capital Market Institute, 2022)
Market Sideways is sometimes difficult to determine purchases using technical analysis indicators that are trending or leading to stock prices, some of the right indicators for Market Sideways are Average Directional Index (ADX), Directional Movement Index (DMI), Average True Range (ATR). The research objective was conducted to explain why it is important using ADX, DMI, and ATR when Market Sideways. Determining whether the market is trending or sideways with parameters from ADX, DMI, and ATR, and after that it explains the buying and selling points even though the Market Sideways is in PT. Bukit Asam Tbk. Otherwise, the implication of this research is that traders know and use optimal strategies using ADX, DMI, and ATR on Market Sideways, also to publish stock recommendations for private and public. The ADX, ATR and DMI indicators from the results of the study showed negative results for decision making in buying or selling shares in PT. Bukit Asam Tbk for the period 2017 - 2018, This research shows that this indicator provides inaccurate directions for buying or selling for investors or traders in the issuer PT. Bukit Asam Tbk, but easy to operate.